MAKNA BUNGA BANK: SEBUAH KAJIAN INTERAKSIONISME SIMBOLIK - Oktavendi, Tri Wahyu (Jurnal Reviu Akuntansi dan Keuangan)
The aim of this research is to understand how the meaning of bank interest according to themanager PT CTU. This research uses symbolic interactionism approach. Through five informants who have a position in PT CTU, researcher found the duality of meaning that contradicteach other. The duality of the meaning is (1) bank interest in return for services and (2) bankinterest as a liability for social activities. The dominant meaning in the contradiction is bankinterest as a liability for social activities due to the power of shareholders.Keywords: Symbolic Interactionism, The Meaning of Bank Interest, Domination of Shareholder.